2014
DOI: 10.1126/science.1252826
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LRRC8 Heteromers as an Essential Component of the Volume-Regulated Anion Channel VRAC

Abstract: Abstract:Regulation of cell volume is critical for many cellular and organismal functions, yet the molecular identity of a key player, the volume-regulated anion channel VRAC, has remained unknown. A genome-wide siRNA screen in mammalian cells identified LRRC8A as a VRAC component. LRRC8A formed heteromers with other LRRC8 multispan membrane proteins.Genomic disruption of LRRC8A ablated VRAC currents. Cells with disruption of all five LRRC8 genes required LRRC8A co-transfection with other LRRC8 isoforms to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
983
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 545 publications
(1,092 citation statements)
references
References 41 publications
56
983
3
1
Order By: Relevance
“…Notably, however we found no evidence for delayed astrocyte maturation or astrogliosis in both Mlc1 ‐null18 and Glialcam ‐null mice (not shown). LRRC8A has recently been identified as an essential component of the mammalian VRAC 35, 36. We found no differences in LRRC8A expression and subcellular localization between wild‐type, Glialcam ‐null and Mlc1 ‐null mice, which does not exclude a functional interaction between the related proteins.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Notably, however we found no evidence for delayed astrocyte maturation or astrogliosis in both Mlc1 ‐null18 and Glialcam ‐null mice (not shown). LRRC8A has recently been identified as an essential component of the mammalian VRAC 35, 36. We found no differences in LRRC8A expression and subcellular localization between wild‐type, Glialcam ‐null and Mlc1 ‐null mice, which does not exclude a functional interaction between the related proteins.…”
Section: Discussioncontrasting
confidence: 77%
“…We extended the immunohistochemical and immuno‐EM analysis to expression of the caveolar lipid raft protein caveolin‐1 and the recently identified VRAC channel component LRRC8A in wild‐type, Glialcam ‐null and Mlc1 ‐null mice 18, 35, 36. We found no differences between mutant and control animals (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…[6][7][8][9][10][11][12] In 2014, 2 research groups independently reported that the leucine-rich repeat containing 8A (LRRC8A), which has 4 transmembrane domains and a leucine-rich repeat (LRR) domain at the C-terminus, is a core factor of VSOR in human cells. 13,14 They reported in common that knockdown of LRRC8A diminished endogenous VSOR currents in human cells, and such reduced currents could be rescued by introduction of exogenous LRRC8A, but overexpression of LRRC8A alone in normal cells paradoxically reduced endogenous VSOR currents. 13,14 Also, VSOR was shown to be a heteromeric channel containing not only LRRC8A but also other LRRC8 family members.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 They reported in common that knockdown of LRRC8A diminished endogenous VSOR currents in human cells, and such reduced currents could be rescued by introduction of exogenous LRRC8A, but overexpression of LRRC8A alone in normal cells paradoxically reduced endogenous VSOR currents. 13,14 Also, VSOR was shown to be a heteromeric channel containing not only LRRC8A but also other LRRC8 family members. 13 Indeed, a multimeric complex mainly of these members with a molecular mass of »800 kDa was found to be sufficient to form the osmo-and ionic strength-sensitive anion channels in lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation